A 2‐element K‐band series‐fed directional antenna array for millimeter wave radar applications. Issue 5 (14th February 2021) - Xia, Zhixin; Cai, Zhanghua; Li, Fuhai; Fan, Jun; Qi, Yihong
Abstract: In this paper, a K‐band series‐fed directional antenna array based on a wide bandwidth, high‐efficiency electromagnetic radiation structure is proposed for millimeter wave radar applications. Only two fundamental elements are needed to meet design specifications. By cutting off one side of the original antennas and using the grounded coplanar waveguide (CPWG) and microstrip hybrid feeding method, a series‐fed structure is innovatively developed to make the designed array simple in structure and efficient in space utilization. Simultaneously, the feed structure of the CPWG and the through‐hole vias around the antenna are proposed in combination to form a semi‐closed shielded cavity structure. It can better constrain the electric field, suppress radiation from the transmission line, alleviate the antenna radiation pattern distortion and reduce the transmission line loss. The similar beamwidth is mainly achieved in both the E‐ and H ‐planes by placing the two elements vertically perpendicular to the H‐plane. The measured relative bandwidth of the antenna array is 24%. Within the designed bandwidth (22‐28 GHz), the measured | S 11 | is lower than −10 dB, and the gain is basically above 10 dBi. The measured E‐ and H‐plane beamwidths are close to each other with a difference of less than 10°for each frequency, while the beamwidth value varies between 32°and 51°in the entire frequency band of 22 to 28 GHz. The simulated results are in good agreement with the measured ones.